Optimization of Ultrasound Assisted Extraction of Bioactive Compounds from Apple Pomace - Itziar Egüés; Fabio Hernandez-Ramos; Iván Rivilla; Jalel Labidi (Molecules, 2021)
In the present work, the optimization of the extraction of antioxidant compounds from apple pomace using ultrasound technology as an environmentally friendly and intensification process was developed. Different sonication powers, extraction temperatures and extraction times were studied and their influence on extraction yield and characteristics of the extracted samples (total phenolic compounds, flavonoid content and antioxidant capacity) are presented. The elaborated experimental design and the analysis of Pareto and response surface diagrams allowed us to determine the optimal extraction conditions. The conditions that allow the maximum extraction of phenolic compounds were found at 20 min, 90 °C and 50% ultrasound amplitude. Nevertheless, at these conditions, the antioxidant capacity measured by DPPH decreased in the extracted samples.